RClim Tool: user manual and video - Llanos Herrera, Lizeth (International Center for Tropical Agriculture, 2014)
RClimtool has been designed with the objective to facilitate the performance of statistical analysis, quality control, filling missing data, homogeneity analysis and calculation of indicators for daily weather series of maximum temperature, minimum temperature and precipitation.